SOCIAL CAPITAL IN NON-BARTER TRANSACTION CHAIN IN PASAR BLANTE KAWANGKOAN, NORTH SULAWESI PROVINCE - Rahel Widiawati Kimbal; Agus Suman; Khusnul Ashar; Asfi Manzilati (Journal of Indonesian Economy and Business (JIEB), 2012)
The research aims to find out the forms as well as the function of social capital in the chain of economic activity in Pasar Blante (Blante market), one of the traditional markets in Kawangkoan, North Sulawesi, particularly its non-barter transaction. This research employs phenomenology-qualitative research method by involving triangulation as the method of data gathering. Spradley Model is chosen to analyze data. The results of the research highlight kinds of social capital embodied in non-barter transaction in Pasar Blante which comprises trust, network, norms. These important factors are reflected in transaction chain involving many agents such as (1) the cattle’s owner; (2) maantung; (3) tukang blante; (4) cukong; and (5) the buyers.The contribution of social capital on non-barter transaction among people involving in economic activity are embodied in (1) The transparent transaction resulting in lower informationcost among people taking part in that activity; (2) Free information access which enables them to obtain credible information on getting qualified cattles with highly economical value; (3) Appreciation on someone’s ownership shown in high-sense of belonging and responsibility ontaking care all cattles in Pasar Blante without additional charge; (4) Commitment on contact agreement which minimizes the cancellation on transaction; (5) The transaction needs no written document which legalizes the ownership of the buyer; (6) The availability of cattle’s food which in turn reduces the cattle’s food consumption cost; (7) Fast access on marketing which is supported by all parties involving in the transaction as well as all elements of society. Moreover, this research elucidates that non-barter transaction also support other transactions such as barter transaction and trade-in transaction. Finally, this non-barter transaction proves to be contributive to increase the local revenues and generates the economic activity in the area.Keywords: social capital, traditional market, transaction, chain, non-barter.